Can Integrated Care Help in Meeting the Challenges Posed on Our Health Care Systems by COVID-19? Some Preliminary Lessons Learned from the European VIGOUR Project - Lindner, Sonja (Int J Integr Care, 2020)
The COVID-19 pandemic puts health and care systems under pressure globally. This current paper highlights challenges arising in the care for older and vulnerable populations in this context and reflects upon possible perspectives for different systems making use of nested integrated care approaches adapted during the work of the EU-funded project VIGOUR (“Evidence based Guidance to Scale-up Integrated Care in Europe”, funded by the European Union’s Health Programme 2014–2020 under Grant Agreement Number 826640).